2016
DOI: 10.4088/jcp.16m10744
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vortioxetine on Cognitive Functioning in Working Patients With Major Depressive Disorder

Abstract: Objective: This post hoc analysis investigates the effect of vortioxetine on cognitive functioning and depressive symptoms in working adults with major depressive disorder (MDD).Methods: Population data from FOCUS, a double-blind, randomized, placebo-controlled study investigating the efficacy of vortioxetine versus placebo on cognitive functioning and depression in patients with MDD, were used to analyze mean change from baseline scores for the Digit Symbol Substitution Test (DSST), Trail Making Test A/B (TMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
9
55
0
Order By: Relevance
“…The significant improvements in both self-reported cognitive symptoms and cognitive performance assessed by the DSST seen in this study are consistent with results of previous studies of vortioxetine and reinforce these findings in a real-life setting. [33][34][35][36][37][38] The significant improvements in work productivity seen in the present study during treatment with vortioxetine are consistent with the findings of the Combined Medications to Enhance Depression Outcomes (CO-MED) trial, which demonstrated that work productivity outcomes improve significantly with antidepressant treatment and that early changes in work productivity are significant predictors of long-term clinical course. 52 In contrast to the results of the European PERFORM study, 43 patient-rated depression severity (QIDS-SR) scores were not found to significantly predict functioning outcomes (SDS or WLQ) when simultaneously adjusting for improvements in cognitive symptom severity (PDQ-D-20 score) at any subsequent timepoint in the current SEM analyses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The significant improvements in both self-reported cognitive symptoms and cognitive performance assessed by the DSST seen in this study are consistent with results of previous studies of vortioxetine and reinforce these findings in a real-life setting. [33][34][35][36][37][38] The significant improvements in work productivity seen in the present study during treatment with vortioxetine are consistent with the findings of the Combined Medications to Enhance Depression Outcomes (CO-MED) trial, which demonstrated that work productivity outcomes improve significantly with antidepressant treatment and that early changes in work productivity are significant predictors of long-term clinical course. 52 In contrast to the results of the European PERFORM study, 43 patient-rated depression severity (QIDS-SR) scores were not found to significantly predict functioning outcomes (SDS or WLQ) when simultaneously adjusting for improvements in cognitive symptom severity (PDQ-D-20 score) at any subsequent timepoint in the current SEM analyses.…”
Section: Discussionsupporting
confidence: 88%
“…29,30 Vortioxetine has been shown to be effective not only for the treatment of MDD, 31,32 but also to improve cognitive symptoms in patients with depression. [33][34][35][36][37][38] A recent meta-analysis showed that vortioxetine also demonstrates efficacy in improving overall functioning and functional remission, as assessed by the Sheehan Disability Scale (SDS), in adults with MDD. 39 Assessment in Work productivity and the Relationship with Cognitive symptoms (AtWoRC) is an interventional, open-label, real-world study undertaken to examine the association between cognitive symptoms and workplace productivity in working Canadian patients with MDD treated with vortioxetine.…”
Section: Introductionmentioning
confidence: 99%
“…A recent preclinical study revealed that the EPO‐associated increase in hippocampal pyramidal neurons and oligodendrocytes was only maintained long‐term (≥6 months) in mice that also received continuous cognitive challenges . This finding is consistent with the demonstration in a cognition trial in unipolar depression that working patients displayed greater cognitive benefits of vortioxetine than those who were unemployed . Taken together, these observations are suggestive of stronger treatment effects on neuroplasticity and cognition in individuals who receive continuous cognitive challenges.…”
Section: Future Perspectivessupporting
confidence: 78%
“…Given this legacy from schizophrenia research, cognition trials in bipolar disorder will need to make decisions about how to define their key secondary (if not co‐primary) measure of functional change. Inclusion of a functional measure would also enable assessment of the potential interaction between functional status and the cognition benefits of an intervention, which would be interesting in light of preliminary evidence for greater treatment‐related cognitive improvement in high‐ vs low‐functioning patients,…”
Section: Resultsmentioning
confidence: 99%
“…[8] Vx significantly improves cognition, independent of depressive symptoms and is an important treatment for MDD-related cognitive dysfunction. [9,10] In patients with MDD the recommended dose range is 5-20 mg / day. [11] Scientists have found that Vx 5-20 mg over 6/8 weeks improves the overall functioning of patients with MDD.…”
Section: Introductionmentioning
confidence: 99%